2014
DOI: 10.1002/adfm.201400773
|View full text |Cite
|
Sign up to set email alerts
|

An All‐Ceramic Solid‐State Rechargeable Na+‐Battery Operated at Intermediate Temperatures

Abstract: 5380 www.MaterialsViews.com wileyonlinelibrary.com e.g. lithium-ion batteries (LIBs), is the cost of lithium. Lithium is a light element neither earth-abundant (ranked the 25 th of the most abundant elements) nor evenly distributed geologically on the earth. It is, therefore, a relatively expensive element, roughly 30 times more expensive than sodium, another light alkaline element. [ 1,2 ] Based on these facts, it would seem to be rational to develop all-solid-state sodium-ion batteries (NIBs) that are advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 28 publications
3
48
0
Order By: Relevance
“…Another strategy is increasing operating temperature so that the ion motion in solid state systems can be enhanced. This approach has been used by Huang et al [236] in an all ceramic rechargeable Na + -ion battery. However, it also presents great engineering challenge for the battery systems.…”
Section: Discussionmentioning
confidence: 99%
“…Another strategy is increasing operating temperature so that the ion motion in solid state systems can be enhanced. This approach has been used by Huang et al [236] in an all ceramic rechargeable Na + -ion battery. However, it also presents great engineering challenge for the battery systems.…”
Section: Discussionmentioning
confidence: 99%
“…This explains the reason why, despite increasing interest in solid-state electrolytes, little progress in solid-state batteries has been reported, with only few publications on oxide-based solid-state sodium batteries567. In the present work, the fabrication of a room temperature solid-state Na-S battery using an oxide electrolyte is demonstrated that represents the first step towards the creation of a solid-state room-temperature Na-S battery.…”
mentioning
confidence: 88%
“…Next-generation rechargeable batteries have been extensively studied as a potential power source for large-scale devices such as electric vehicles (EVs), hybrid electric vehicles (HEVs), and smart grids 1 2 3 4 . In addition, Na-ion batteries (NIBs) have recently received significant attention owing to their low cost and abundant global reserves compared to those of Li-ion batteries (LIBs) 5 6 7 8 9 10 . However, Na ion have a larger ionic radius and molar mass than Li ion; hence, NIBs exhibit lower specific capacity and rate capability, larger volume change, and shorter cycling life than LIBs 11 12 13 .…”
mentioning
confidence: 99%